Xylooligosaccharides production by optimized autohydrolysis, sulfuric and acetic acid hydrolysis for minimum sugar degradation production - Forsan, Carolina Froes [UNESP] (2021)
Xylooligosaccharides (XOS) acts as a prebiotic, a food component that is not digested but stimulates the growth of beneficial microorganisms present in the intestine, such as bifidobacteria and lactobacilli, improving the health of the host. This study obtained XOS by comparing optimized conditions for acid hydrolysis and autohydrolysis of sugarcane bagasse, showing that is possible to produce XOS with minimum degradation of sugras. The acid hydrolysis process varied the parameters applying a 23 factorial design using 1–3% (m/v) sulfuric or acetic acid; a temperature of 100–160 °C and a reaction time of 15–55 min. The autohydrolysis was performed by 22 factorial design using the same range of temperature and time. The acetic acid hydrolysis of the sugarcane bagasse resulted in the conversion of xylan into XOS of 18.41% (m/m) with 1% (m/v) acid at 100 °C for 15 min, with xylopentaose/xylohexaose predominance. The hydrolysis of sugarcane bagasse with sulfuric acid resulted in 90.13% (m/m) of XOS with 2% (m/v) of acid at 79.55 °C for 35 min, with xylobiose prevalence. Autohydrolysis of bagasse resulted in 13.67% (m/m) xylan conversion into XOS at 172.4 °C for 35 min, with xylotetraose prevalence. The degradation sugar products were low for the conditions studied, with 0.31%, 0.16%, and 0.01% (m/m) of furfural using sulfuric, acetic, and autohydrolysis, successively. The results demonstrated that XOS with different degrees of polymerization can be produced applying specific pretreatment conditions of autohydrolysis, sulfuric, and acetic acid, with the minimum content of sugar degradation.